Strategic Management for Long-term Sustainability in Higher Education Institutions - Dodhy Hyronimus; Adiatma, Tini (PT. Inovasi Teknologi Komputer, 2024)
The purpose of writing this article is to find out references regarding strategic management in higher education. This research was conducted using the Systematic Literature Review method. The articles used were obtained from the Scopus database with a specific search, namely